2010
DOI: 10.4028/www.scientific.net/msf.663-665.666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidant/Monomer Ratio on Conductivity of Ferric Chloride Oxidized Polypyrrole

Abstract: A series of polypyrrole samples were synthesized by oxidizing pyrrole in the aqueous medium of ferric chloride, and the relation between oxidant/monomer ratio and the electrical conductivity of polypyrrole was studied by increasing the ratio from 0.25:1 to 2.5:1. Our results showed that the conductivity of polypyrrole was dependent on the mole ratio of the oxidant to pyrrole, and a maximum value for electrical conductivity of 1500 S/m was achieved for a ratio of 0.75:1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…The electrical conductivity of polypyrrole was studied by Huang et al, who reported that the electrical conductivity of PPy depends on the molar ratio of oxidant (FeCl 3 ) to pyrrole monomer, reaching a maximum for a molar ratio of 0.75:1. 5 Batool et al prepared a PPy-hematite magnetic composite by a simple chemical oxidation technique with different weight percentages of hematite in a PPy matrix during the polymerization of pyrrole monomers, reporting that intercalation of the insulating inorganic hematite phase into the PPy matrix induced novel properties such as transforming PPy from a weak antiferromagnetic to ferromagnetic material. 6 Organic semiconductors (OSCs) are a type of electronic materials that have attracted much interest over recent decades because of their technological uses owing to their performance advantages compared with conventional semiconductors for largearea device applications.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivity of polypyrrole was studied by Huang et al, who reported that the electrical conductivity of PPy depends on the molar ratio of oxidant (FeCl 3 ) to pyrrole monomer, reaching a maximum for a molar ratio of 0.75:1. 5 Batool et al prepared a PPy-hematite magnetic composite by a simple chemical oxidation technique with different weight percentages of hematite in a PPy matrix during the polymerization of pyrrole monomers, reporting that intercalation of the insulating inorganic hematite phase into the PPy matrix induced novel properties such as transforming PPy from a weak antiferromagnetic to ferromagnetic material. 6 Organic semiconductors (OSCs) are a type of electronic materials that have attracted much interest over recent decades because of their technological uses owing to their performance advantages compared with conventional semiconductors for largearea device applications.…”
Section: Introductionmentioning
confidence: 99%
“…PPy/MWCNT composites were synthesized by oxidative chemical polymerization using ferric chloride (FeCl 3 •6H2O) as oxidant [13,[20][21][22]. Oxidant to monomer mole ratio is controlled to 0.75 in order to achieve high pyrrole conductivity [23]. MWCNT (100 mg) was first dispersed into deionized water with 20% methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The capacitor behavior as well as the total equivalent resistance (ESR) and the ionic transfer resistance (R ct ) at the electrode/electrolyte interface can be evaluated at the low and high frequency region respectively [8,23,25]. Bode plot and complex capacitance plot were used to further evaluate the capacitive performance in device setup [26,27].…”
Section: Cyclic Voltammetry (Cv)mentioning
confidence: 99%
See 1 more Smart Citation